Implementasi Aplikasi Pear Deck Sebagai Evaluasi Pembelajaran dalam Pembelajaran Menulis teks Berita Siswa kelas VII MTs Miftahul Qulub - Zainuri Ihsan; Liana Rochmatul Wachidah; Moh. Hafid Effendy; Mochamad Arifin Alatas (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Learning evaluation is an essential component in education because it functions to measure students' competency achievements and provide feedback to improve the quality of learning, especially in writing skills that require clear structure, language accuracy, and critical thinking ability. This study aims to explore the application of the Pear Deck application as an evaluation medium in teaching news writing to seventh-grade students at MTs Miftahul Qulub. This study uses a descriptive qualitative approach with a subject group of 28 students. The research design is exploratory, encompassing the planning stage, implementation of Pear Deck-based learning, and evaluation of student assignment results. The data collection instruments consist of observation sheets, interview guidelines, and documentation. Data were analyzed using the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawing, and were validated with triangulation techniques. The research results show that Pear Deck is capable of increasing student participation and literacy. Interactive evaluative activities and assignments based on actual events encourage the systematic application of the 5W+1H principle. More than 80% of students achieved good to very good results, affirming the effectiveness of Pear Deck in supporting writing skills and active learning. Based on these findings, it is recommended that educators, particularly Indonesian language teachers, integrate Pear Deck media into writing skills evaluation activities as an effort to encourage active student engagement and improve the quality of learning outcomes.Evaluasi pembelajaran merupakan komponen esensial dalam pendidikan karena berfungsi mengukur pencapaian kompetensi siswa serta memberikan umpan balik untuk meningkatkan kualitas pembelajaran, khususnya dalam keterampilan menulis yang menuntut struktur yang jelas, ketepatan bahasa, dan kemampuan berpikir kritis. Penelitian ini bertujuan mengeksplorasi penerapan aplikasi Pear Deck sebagai media evaluasi pada pembelajaran menulis teks berita bagi siswa kelas VII MTs Miftahul Qulub. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan subjek sebanyak 28 siswa. Desain penelitian bersifat eksploratif, mencakup tahap perencanaan, pelaksanaan pembelajaran berbasis Pear Deck, dan evaluasi hasil tugas siswa. Instrumen pengumpulan data terdiri atas lembar observasi, pedoman wawancara, dokumentasi. Data dianalisis dengan model Miles dan Huberman melalui tahapan reduksi, penyajian, dan penarikan kesimpulan, serta divalidasi dengan triangulasi teknik. Hasil penelitian menunjukkan bahwa Pear Deck mampu meningkatkan partisipasi dan literasi siswa. Aktivitas evaluatif interaktif dan penugasan berbasis peristiwa aktual mendorong penerapan prinsip 5W+1H secara sistematis. Lebih dari 80% siswa memperoleh hasil baik hingga sangat baik, menegaskan efektivitas Pear Deck dalam mendukung keterampilan menulis dan pembelajaran aktif. Berdasarkan temuan tersebut, direkomendasikan agar pendidik, khususnya guru Bahasa Indonesia, mengintegrasikan media Pear Deck dalam kegiatan evaluasi keterampilan menulis sebagai upaya untuk mendorong keterlibatan aktif siswa dan meningkatkan mutu capaian pembelajaran.